Evidence for the effects of neonicotinoids used in arable crop production on non-target organisms and concentrations of residues in relevant matrices: a systematic map protocol. Issue 1 (December 2016) - James, Katy; Randall, Nicola; Walters, Keith; Haddaway, Neal; Land, Magnus
Abstract Background Neonicotinoid insecticides (NNIs) have been routinely used in arable crop protection since their development in the early 1990s. These insecticides have been subject to the same registration procedures as other groups of pesticides, thus meet the same environmental hazard standards as all crop protection products. However, during the last 10 years the debate regarding their possible detrimental impact on non-target organisms, particularly pollinators, has become increasingly contentious and widely debated. Against this background, legislators and politicians in some countries, have been faced with a need to make decisions on the future registration of some or all of this class of insecticides, based on published evidence that in some areas is incomplete or limited in extent. This has created much concern in agricultural communities that consider that the withdrawal of these insecticides is likely to have significant negative economic, socio-economic and environmental consequences. Methods The proposed systematic map aims to address the following primary question: What is the available evidence for the effects of neonicotinoids used in arable crop production on non-target organisms and concentrations of residues in relevant matrices? The primary question will be divided into two sub-questions to gather research literature for (1) the effect of NNIs on non-target organisms (2) the occurrence of concentrations of NNIs in matrices of relevance to non-target organisms (i.e. exposure routes). The systematic map will focus on NNIs used in arable crop production: imidacloprid, clothianidin, thiamethoxam, acetamiprid, thiacloprid and dinotefuran. Separate inclusion criteria have been developed for each sub-question. Traditional academic and grey literature will be searched for in English language and a searchable databases containing extracted meta-data from relevant included studies will be developed.